2017
DOI: 10.1111/mbe.12144
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Baby: Foreign Language Intervention in Madrid's Infant Education Centers

Abstract: The first years of life represent a unique window of opportunity for foreign language learning. However, key questions are: How much and what kind of foreign language exposure is needed to ignite learning? We conducted a foreign language (English) intervention in four public Infant Education Centers in Madrid, Spain. Intervention children (N = 126, ages 7–33.5 months) experienced 18 weeks of daily, hour‐long, group English sessions with native‐speaking tutors, using a brain‐based method of infant language deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 58 publications
(72 reference statements)
1
27
0
2
Order By: Relevance
“…La creencia según la cual el aprendizaje de dos lenguas puede alterar o retrasar el desarrollo del lenguaje y producir fracaso escolar no tiene soporte empírico (Ferjan Ramírez y Kuhl, 2017). La revisión realizada por Bialystok et al (2012) deja en evidencia que el desempeño de llos niños bilingües es superior, especialmente en aquellas tareas que requieren manipulación de símbolos y reorganización.…”
Section: Neuromito 1: Se Debe Adquirir La Lengua Materna Antes De Aprunclassified
See 1 more Smart Citation
“…La creencia según la cual el aprendizaje de dos lenguas puede alterar o retrasar el desarrollo del lenguaje y producir fracaso escolar no tiene soporte empírico (Ferjan Ramírez y Kuhl, 2017). La revisión realizada por Bialystok et al (2012) deja en evidencia que el desempeño de llos niños bilingües es superior, especialmente en aquellas tareas que requieren manipulación de símbolos y reorganización.…”
Section: Neuromito 1: Se Debe Adquirir La Lengua Materna Antes De Aprunclassified
“…También muestra mejor capacidad para resolver problemas lingüísticos (conciencia metalingüística) y problemas no verbales que requerían que se ignorara información engañosa. Es más, el estudio de Ferjan Ramírez y Kuhl (2017), en el que se utiliza magnetoencefalografía (MEG, por sus siglas en inglés) muestra, que cuando está expuesto a dos idiomas, el cerebro infantil es igualmente capaz de aprenderlos de manera simultánea. De hecho, niñas y niños bilingües desarrollan habilidades de vocabulario iguales o superiores a las de sus pares monolingües.…”
Section: Neuromito 1: Se Debe Adquirir La Lengua Materna Antes De Aprunclassified
“…Research findings, however, have consistently shown the positive impact of bilingualism on higher executive functions, i.e., multi-tasking Yang, Yang, & Lust, 2011), creativity (Adi-Japha, Berberich-Artzi, and Libnawi, 2010), spatial perspective taking (Greenberg, Bellana, and Bialystok, 2013), and conflict resolution tasks (Carlson and Meltzoff, 2008). More importantly, these advantages are noticed as early as the first few months of children's lives (Ferjan Ramírez, and Kuhl, 2017;Kovacs and Mehler, 2009).…”
Section: Bilingualism In Early Childhoodmentioning
confidence: 99%
“…At a very young age, the brain plasticity is still strongly reliant on environmental impacts and the brain networks have not fully evolved. Ramirez & Kuhl (2017) found that with intervention activities carried out with high interaction intensity, such as listening and playing with native speaker tutors, preschoolers grow EFL vocabulary comprehension and produce vocalization.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that acquiring language including FL indeed depends on several aspects, such as social environment (Beller, 2008), sufficient input and interaction (Ramirez & Kuhl, 2017) to develop both the language structure and the pragmatic side of the intended language. Interaction and social environment facilitates the complicated language learning pathways, because it strengthens the relationship between words and their references (Verga & Kotz, 2013), words and their meaning, pragmatics and pronunciation (Conboy et al, 2015) thus it influences children's language development (Ramirez & Kuhl, 2017). Meanwhile authentic input from the target language contributes practical and cultural target language for children to acquire (Pinsonneault, 2008).…”
Section: Introductionmentioning
confidence: 99%